2016
DOI: 10.1016/j.jgeb.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of Fusarium sp. using ITS and RAPD causing fusarium wilt of tomato isolated from Assam, North East India

Abstract: Fusarium oxysporum which causes wilt is a serious pathogen. Fusarium isolates were isolated from Assam located in North East region of India. Morphological identification of Fusarium isolates was done using conidial and hyphal structures. Molecular identification of Fusarium isolates was done by amplifying the internal transcribed spacer (ITS) region of the conserved ribosomal DNA using primers ITS1 and ITS4. All the ITS sequences were compared for gaps and similarity. Further, characterization of random ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 29 publications
5
34
0
3
Order By: Relevance
“…Then, in order to give more resolution to this complex and differentiate EA-FP0013 from the other species, two other molecular markers were selected, EF and Btub. These markers have been used for many researchers around the world with successful results [23], [24], [25]. A phylogenetic analysis was carried out with concatenated genes and, through the ML and BI methodologies, a single phylogenetic tree was obtained (Figure 4).…”
Section: Gene Sequence Analysis and Molecular Phylogeneticsmentioning
confidence: 99%
“…Then, in order to give more resolution to this complex and differentiate EA-FP0013 from the other species, two other molecular markers were selected, EF and Btub. These markers have been used for many researchers around the world with successful results [23], [24], [25]. A phylogenetic analysis was carried out with concatenated genes and, through the ML and BI methodologies, a single phylogenetic tree was obtained (Figure 4).…”
Section: Gene Sequence Analysis and Molecular Phylogeneticsmentioning
confidence: 99%
“…In addition it can be done crop rotation, balanced fertilization, avoid giving high N and low K, and good drainage to prevent attacks. Biological control can also be carried out with Tric hoderma sp antagonists [13].…”
Section: ) Stem Rot (Fusarium Sp)mentioning
confidence: 99%
“…Lin et al (2014) used ITS as a molecular marker for identification of the F. verticillioides and F. proliferatum associated with sugarcane infection in Pokkah Boeng, China. Recently, Singha et al (2016) demonstrated that molecular profiling using ITS is an indispensable method for rapid identification of Fusarium sp. isolated from Fusarium-wilt of tomato from Assam, North East India.…”
Section: Upgma Analysismentioning
confidence: 99%